A Neglected Pioneer: Carla Serena (1820-1884): (Travels in Imereti, Mingrelia, Samurzakano, Abkhazia, Kakheti, Guria, and the districts of Gori, Borjomi, and Akhaltsikhe, 1876 -77 and 1881) - Peter Skinner (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2026)
The article discusses foreign female travelers, whether known or unknown to Georgian readers, who visited various parts of Georgia, made important notes, and introduced Georgia and its culture to the world.